Relações intergeracionais: palavras que estimulam - Santos, Divina de Fátima dos (2010)
The dissertation is a study about the content of letters used as a means of communication between the elderly and children, analyzing the type of interaction experienced between them and identifying the meanings of this exchange. This is a qualitative study based on interviews with elderly and on data collected from letters written by students of adult education (Education for Youths and Adults) with ages ranging from 18 to 72 years in literacy process and the regular education children aged between 8 and 10 years who attended one of the units of the network SESI-SP - Social Service Industry of São Paulo. The exchange of letters between these students occurred during the years 2008 and 2009. The matters covered in the letters started several discussions, and to facilitate understanding, in this study they are presented in the form of topics such as religion, dreams, the right words, the world of work and retirement, the otherness, the pictographic communication, the communication by symbols and the exchange of glances, all equally compelling, because they caused reflections by both the children and the elderly. The analysis of the data makes it possible to determine the characteristics of the subjects involved and indicates that the exchange of letters promotes interaction among students, as well as the process of changing attitudes and building ethical values that are very important in school, family and social life of both the elderly and the participating children. The changes through these experiences can provide or facilitate a healthier coexistence between different generations within the school and the various social spaces of everyday life. These findings indicate the importance of interdisciplinary studies with focus on the question of the relationship between generations